Specific Caleosin/Peroxygenase and Lipoxygenase Activities Are Tissue-Differentially Expressed in Date Palm (Phoenix dactylifera L.) Seedlings and Are Further Induced Following Exposure to the Toxin 2,3,7,8-tetrachlorodibenzo-p-dioxin - Hanano, Abdulsamie; Almousally, Ibrahem; Shaban, Mouhnad; Rahman, Farzana; Hassan, Mehedi; Murphy, Denis J. (Frontiers in Plant Science, 2017)
Two caleosin/peroxygenase isoforms from date palm, Phoenix dactylifera L., PdCLO2 and PdCLO4, were characterised with respect to their tissue expression, subcellular localisation and oxylipin pathway substrate specificities in developing seedlings. Both PdCLO2 and PdCLO4 had peroxygenase activities that peaked at the mid-stage (radicle length of 2.5 cm) of seedling growth and were associated with the lipid droplet (LD) and microsomal fractions. Recombinant PdCLO2 and PdCLO4 proteins heterologously expressed in yeast cells were localised in both LD and microsomal fractions. Each of the purified recombinant proteins exhibited peroxygenase activity but they were catalytically distinct with respect to their specificity and product formation from fatty acid epoxide and hydroxide substrates. We recently showed that date palm CLO genes were upregulated following exposure to the potent toxin, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) (Hanano et al., 2016), and we show here that transcripts of 9- and 13-lipoxygenase (LOX) genes were also induced by TCDD exposure. At the enzyme level, 9-LOX and 13-LOX activities were present in a range of seedling tissues and responded differently to TCDD exposure, as did the 9- and 13-fatty acid hydroperoxide reductase activities. This demonstrates that at least two branches of the oxylipin pathway are involved in responses to the environmental organic toxin, TCDD in date palm.